MEASURING LONGITUDINAL WRITING DEVELOPMENT USING INDICES OF SYNTACTIC COMPLEXITY AND SOPHISTICATION. Issue 4 (27th September 2021) - Kyle, Kristopher; Crossley, Scott; Verspoor, Marjolijn
Abstract: Measures of syntactic complexity such as mean length of T-unit have been common measures of language proficiency in studies of second language acquisition. Despite the ubiquity and usefulness of such structure-based measures, they could be complemented with measures based on usage-based theories, which focus on the development of not just syntactic forms but also form-meaning pairs, called constructions (Ellis, 2002 ). Recent cross-sectional research (Kyle & Crossley, 2017 ) has indicated that indices related to usage-based characteristics of verb argument construction (VAC) use may be better indicators of writing proficiency than structure-based indices of syntactic complexity. However, because cross-sectional studies can only show general trends across proficiency benchmarks, it is important to test these findings in individuals over time (Lowie & Verspoor, 2019 ). Thus, this study investigates the developmental trajectories of second language learners of English across two academic years with regard to syntactic complexity and VAC sophistication.